Leuca-fence: Living fence for sheep using Leucaena leucocephala - Sumberg, J.E. (1983)
Describes construction features of a `live' Leucaena leucocephala fence, developed by ILCA as part of its Small Ruminant Programme in Ibadan, Nigeria, that has been successfully used in restraining the movements of sheep.